Policies for Overcoming The Environmental Damage Due to Forest Conversion in Bima, West Nusa Tenggara - Didik Irawansah; Absori Absori; Wardah Yuspin (Jurnal Hukum Volkgeist, 2022)
Environmental damage caused by forest conversion in Bima was quite worrying, the impacts were quite diverse. preliminary observations found that Bima Regional Forests were mostly critical because of conversion. On the other hand, there were no visible signs for stopping the natural disasters. Research Objectives: first; to describe an environmental damage of forest conversion; second; to describe policies on overcoming environmental damage and concepts in tackling the sustainable development. Research method were qualitative analysis. The results of this study, environmental damage in Bima were caused by illegal logging, forest encroachment, land conversion by farmers. The factors are due to economic demands, lack of public awareness, lack of socialization from the government, in overcoming prevention and enforcement, in terms of policies carried out by: 1) Mitigation, especially in residential areas, 2) Reforestation; 3) tracing or installation of supporting stones in deforested areas; 4) socialization and guidance, by calling the community to be educated and given knowledge about forest utilization and sustainability, 5) distributing circulars, 6) spraying plants planted on forest land that is functioned.